The Transformation of Child-Rearing Practices in Digital Families: A Contemporary Family Sociology Perspective - Faza Qurratu Aini (Socious Journal, 2026)
Digital transformation has fundamentally altered the structure and dynamics of the modern family, including the child-rearing patterns adopted by parents in the information technology era. This article examines the shifting patterns of child-rearing in digital families through the lens of contemporary family sociology. Using a systematic literature review approach, this study analyzes how the penetration of digital technology encompassing the internet, mobile devices, social media, and streaming platforms has reconfigured parental roles, mediation strategies, family communication, and the parenting values transmitted to children. The findings show that digital families face a dilemma between leveraging technology as a parenting resource and managing the risks of exposure to negative content, device addiction, and the fragmentation of face-to-face relationships. Parenting strategies are shifting from conventional authoritarian patterns toward active mediation and democratic digital co-regulation. The Indonesian context displays distinctive features, in which local cultural values, extended family structures, and urban–rural disparities shape significant variation in digital parenting patterns. The novelty of this study lies in its integration of parental mediation theory, Bronfenbrenner's ecological theory, and a contemporary family sociology perspective within a single, cohesive analytical framework for understanding the phenomenon of digital families in Indonesia